Application of acoustic sensing and signal processing for PD detection in GIS - Haque, E.; Darus, Ahmad; Yaacob, M.M.; Ahmed, Feroz (1997)
The presence of free moving metallic particles and discharges deteriorates the insulation strength of a compressed SF6 (sulphur-hexafluoride) gas insulated switchgear (GIS) and causes serious limitation in its practical application. Free moving metallic particles and other defects inside the GIS cause partial discharge (PD) which can degrade the insulating properties of the insulant gas SF6 to such an extent that breakdown may occur in the GIS system. So, it is necessary to detect partial discharge in the GIS at an early stage before system failure and extensive damage to the equipment and the rest of the power system. Partial discharge emits acoustic signals which can be detected by applying an acoustic emission sensor (AE sensor) outside the GIS chamber. This paper initially describes some fundamental aspects related to PD detection. Finally, the development of an acoustic PD detection system and some experimental investigations are presented